Female Consumers Recreational Shopping Experiences - Singh, Sarbjot; Sinha, Piyush Kumar; Mishra, HariGovind (International Research Journal of Business Studies, 2013)
The study examines the core meaning of intrinsic shopping to understand their experimental aspects of recreational and leisureshopping. The study focus only on female shoppers of age group ranging from 25-30, and understand their mall experiences becausethis segment is newly transform into self dependent segment which have less social and familial liabilities and have enough enthusiasm to explore the world or their boundaries. The Grounded theory use for identification of recreational shopping themes which are (a) seeking experiences and (b) experimental shopping and each have respective sub themes. The themes are connected to the key idea that shoppers are motivated by their expectations and desires. The study uses social constructivism to find and understand the shopper meanings in real terms rather than imposing and judgment on them. The findings described the way people do recreational shopping and how shopping malls use as leisure space and become facilitators of recreational shopping activities. Females use malls to fulfill their recreational and leisure shopping experiences as this is the great way of enjoying shopping for females of small towns. In malls females not only enjoy product experiences but services experiences also which makes theirshopping interesting. The way the female of this age category use malls help the marketers and retailers to understand this segment shopping patterns.